MANAJEMEN LIKUIDITAS PERBANKAN SYARIAH - Elfadhli, Elfadhli (JURIS (Jurnal Ilmiah Syariah), 2012)
There are some factors to be concerned and anticipated by the bank morder to maintain the bank liquidity. It must be realised that Islamic banking is a new beginning industry, it still unable to be a leader in industry of banking particular in Indonesia. Based on that reality, there fare in this liquidity issue, beside being competitive to other Islamic banking, this competition also happen to conventional banking. There are three ways of anticipating and overcoming the problem of liquidity if we relate it to the efforts of developing Islamic banking, customer needs, profesionality, profitability rate and obedient to the Islamic system : to boost the education and the socialization of Islamic banking specially explaining about economic aspects and Islamic values system to the society, to revise and to enhance work of Islamic banking, and to strengthen the coordination, communication and understanding of customer and bisnis partner, to identity some rationale customer in the bank, and to desain bank portofolio include the instrument liquid.